PERAN PEMERINTAHAN DESA DALAM MENGATASI PERBAIKAN GIZI DI DESA BANTARSARI KABUPATEN BEKASI - Hervina, Firli; Prihesnanto, Fajar; Nadhirah Qintharah, Yuha (Universitas Islam 45 Bekasi, 2023)
The implementation of community service carried out in Bantarsari Village is related to the Role of the Village Government in Addressing Nutrition Improvement. In carrying out the service, it uses community education methods in the form of counseling. Community service was carried out for a month at the location in Kampung Pulo Kecil in Bantarsari Village. The results of the service implementation show that the community, especially parents, don’t know and don’t understand the ways and steps to prevent and minimize stunting, increase community enthusiasm to maintain a healthy lifestyle and good parenting, increase awareness of the child's growth process. The role of government is very important in overcoming nutrition problems, and the need for cooperation and support from government officials to achieve the goal of improving optimal nutrition starts from an early age. In the health services provided, such as services for pregnant women, health for babies, children and others. Apart from providing good nutrition for children, parents also need to have sufficient knowledge and maintain a healthy and well-developed body so that they can prevent nutritional health problems, namely stunting.